Analyzing and evaluating the content of grammatical rules according to the functional approach in series of Al- Arabiya Bain yadaik Text book3 - Hashem, Gamal Ahmed; Mai, Mohammed Youssif; Eltigani, Mohammed Abdelaziz Ahmed (Journal of Educational and Psychological Sciences, 2022)
The current study aims to verify the inclusion of the functional approach specifications in the grammar lessons in the third student book of (Al Arabia Bain Yadaik) series. To achieve this goal, the study followed the descriptive analytical approach using the content analysis tool; The researcher designed a list of specifications for the functional approach; The list was judged by 23 arbitrators, and then the researcher designed a form to evaluate the grammar rules in the third student book of (Al Arabia Bain Yadaik) series, according to the functional approach specifications. The results of the study showed that the functional specifications that must be available in the grammatical content of the curricula of non-Arabic speaking students fall within nine domains, and these domains include 32 descriptions, The functional specifications were available in the book with a total percentage of (55.77) as for the domains; First came the domain of necessity with a percentage of (85%), then the area of the principle of commonness with a percentage of (85%), both of which were graded (very good), and thirdly the domain of examples and its effectiveness with a percentage of (70.83%), then the domain of appropriateness by (70%), and both were graded (good). However, the rest of the domains got less than (50%), and those are the level of application by (46.66%), the domain of training and its effectiveness by (46.25%), the seventh is the domain of goals (40%), and the eighth is the domain of gradation by (38.75%) Finally, the area of interdependence and integration by (27.5%), all with a verbal rating (weak). Based on these results, the researcher recommends using the list of specifications in evaluating and redeveloping the grammar course of (Al Arabia Bain Yadaik) series to conform to the specifications of the functional approach.
Keywords: Functional approach; functional grammar; Al- Arabia Bain Yadaik series; content analysis; evaluation; grammar content; grammatical rules